Beyond EDSA, episodes 1-8 - Jacob, Malou (Manila Communication Foundation for Asia)
An 8-part TV series that tackles the extraordinary events that happened to the Filipino people at EDSA on February of 1986. Each episode is composed of a story telling portion, an inspiring musical number and an in-depth interview with key people during the revolution.
Keywords: Philippines -- History -- Revolution, 1986.; Philippine history